2012
DOI: 10.1371/journal.pone.0034320
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane Fusion Protein αSNAP Is a Novel Regulator of Epithelial Apical Junctions

Abstract: Tight junctions (TJs) and adherens junctions (AJs) are key determinants of the structure and permeability of epithelial barriers. Although exocytic delivery to the cell surface is crucial for junctional assembly, little is known about the mechanisms controlling TJ and AJ exocytosis. This study was aimed at investigating whether a key mediator of exocytosis, soluble N-ethylmaleimide sensitive factor (NSF) attachment protein alpha (αSNAP), regulates epithelial junctions. αSNAP was enriched at apical junctions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 91 publications
2
46
0
Order By: Relevance
“…30,31 Since several recent studies suggested that the Golgi can supply membranes to the autophagic pathway, 12,14,37-39 we investigated if disintegration of this organelle can contribute to the increased autophagic flux in αSNAP-deficient cells. Using HeLa-GFP-LC3 cells, we observed that formation of autophagosomes after αSNAP knockdown occurred in parallel to fragmentation of both cys and trans-Golgi compartments as visualized by giantin and TGN46 labeling, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…30,31 Since several recent studies suggested that the Golgi can supply membranes to the autophagic pathway, 12,14,37-39 we investigated if disintegration of this organelle can contribute to the increased autophagic flux in αSNAP-deficient cells. Using HeLa-GFP-LC3 cells, we observed that formation of autophagosomes after αSNAP knockdown occurred in parallel to fragmentation of both cys and trans-Golgi compartments as visualized by giantin and TGN46 labeling, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, do not understand how loss of αSNAP results in the decreased expression of mTOR or 4E-BP1 as well as some other proteins (Bcl-2 and p120-catenin) described in our previous publications. 30,31 Future studies are required to address this important question.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations